Relationship between knowledge and attitude toward travel health preparation behaviour of air travellers during COVID-19 pandemic - Alhaque, Nitya Fithra Salsabila; Savitri, Pritha Maya; Muti, Annisa Farida; Hadiwiardjo, Yanti Harjono (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2023)
COVID-19 is a highly contagious disease. People who travel in this situation, including air travel, can increase the risk of transmitting or being transmitted by COVID-19. The attack rate of COVID-19 during air travel is 4.8%. It is necessary to form a new behaviour regarding good health preparation before travelling to prevent the spread of COVID-19. A person's behaviour can be affected by knowledge and attitude. This research aims to determine the relationship between knowledge and attitude towards the travel health preparation behaviour of air travellers during the COVID-19 pandemic. This research is an observational analytical study with a cross-sectional approach. The population in this study was people who travelled by air from Soekarno-Hatta International Airport during the COVID-19 pandemic, with inclusion sample criteria of people who travelled by air in June – October 2021 and were aged 15–64 years old. The sample was collected using a purposive sampling technique using social media, and 104 respondents were obtained. The data was collected using an online questionnaire via a Google form. The result shows that the majority of respondents have good knowledge (44.2%), a positive attitude (59.6%) and good behaviour (76%). There was no significant relation between knowledge and behaviour (p=0.066) and a significant relation between attitudes and behaviour (p=0.000). This result can be caused by several factors influencing behaviour, such as other predisposing factors (besides knowledge and attitudes), enabling factors, and reinforcing factors, such as easy access to massive information about the COVID-19 pandemic and strict government regulation.